2015
DOI: 10.1590/0034-7167.2015680116p
|View full text |Cite
|
Sign up to set email alerts
|

Auriculoterapia Chinesa para melhoria de qualidade de vida de equipe de Enfermagem

Abstract: Individualized auriculotherapy (G3) had greater effect compared to the protocol auriculotherapy (G2) for reducing stress and improving life quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 7 publications
0
23
0
16
Order By: Relevance
“…As one of the CTM practices, it uses specific auricular points to treat disorders employing needles, seeds, or magnets to stimulate energetic points. 32,33 Studies have shown this technology's efficacy and effectiveness to cope with stress among nursing workers. A clinical trial reports that auriculotherapy with needles or seeds produced a positive impact on the coping skills of a nursing staff.…”
mentioning
confidence: 99%
“…As one of the CTM practices, it uses specific auricular points to treat disorders employing needles, seeds, or magnets to stimulate energetic points. 32,33 Studies have shown this technology's efficacy and effectiveness to cope with stress among nursing workers. A clinical trial reports that auriculotherapy with needles or seeds produced a positive impact on the coping skills of a nursing staff.…”
mentioning
confidence: 99%
“…In the comparative analyses between the Chinese and French-guided interventions, we found that both types showed very similar effects in reducing pain severity, pain interference with daily activities and physical incapacity. TA B L E 1 Sample characterisation according to sociodemographic and clinical variables associated to pain, according to the instrument of participant characterisation body in the auricular pavilion (Gori & Firenzuoli, 2007) circulating flow of Qi (Kurebayashi & Silva, 2015), consequently promoting pain relief. Furthermore, Chinese EA proposes treatment individualisation, in order to obtain a more balanced and stable energy condition, which is fundamental to avoid disease establishment (Kurebayashi & Silva, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 1 Sample characterisation according to sociodemographic and clinical variables associated to pain, according to the instrument of participant characterisation body in the auricular pavilion (Gori & Firenzuoli, 2007) circulating flow of Qi (Kurebayashi & Silva, 2015), consequently promoting pain relief. Furthermore, Chinese EA proposes treatment individualisation, in order to obtain a more balanced and stable energy condition, which is fundamental to avoid disease establishment (Kurebayashi & Silva, 2015). Accordingly, it has already been reported that individualised EA has a superior effect (when compared to the intervention performed with fixed points) to manage not only pain, but also stress and life quality (Kurebayashi & Silva, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations